Determinants of Foreign Direct Investment in Indian Markets - Shah, Dinal Dinesh (2008)
ABSTRACT Today, India has come a long way since its Independence from the British Government in 1947. The current reform measures undertaken by the Indian Government and its constant effort to integrate the economy with the global market has led to rebirth of interest in FDI in India. The investment climate in the country is surely conducive to foreign investment. The policy liberalization in the country has led to the emergence of more inward foreign investment into the country.